Новий фрагмент латинського напису з Херсонеса - Зубар, В.М.; Антонова, І.А. (Археологія, 1996)
У статті розглядається новий фрагмент надгробка Аврелія Демаса, знайдений у 1990 р., і подається нова інтерпретація його латинської епітафії. Статья посвящена публикации нового фрагмента латинской надписи, обнаруженной в ходе раскопок на территории так называемой цитадели Херсонеса в 1990 г. Этот фрагмент является еще одной частью надгробия с эпитафией Аврелия Демаса, два фрагмента которого были найдены ранее и изданы Э. И. Соломоник. На осповании нового фрагмента вся эпитафия может быть интерпретирована следующим образом: «При жизни себе (и своим близким) Аврелий Демас, ветеран, (проживший) 72 (года), поставил эпитафию». На основании палеографии надпись датируется временем не ранее первой половины ІІІ в. и являстся новым важным источником по вопросу о присутствии ветеранов римской армии в составе гражданского населения Херсонеса. Некоторые особенности языка надписи и оформления надгробия позволяют говорить об определенных характерных чертах процесса романизации населения Херсонеса в первые века н.э. The paper is devoted to description of a new fragment of the Latin inscription found during excavations in the territory of the so-called citadel of the Chersonese in 1990. The fragment is one part more of the epitaph made by Aurelius Demasus, two fragments of which were found earlier and published by Е. I. Solomonik. The new fragment permits the whole epitaph to be interpreted as follows: «In his lifetime Aurelius Demasus, a veteran, (who lived) 72 (years), made this epitaph for himself and his (relatives)». Based on paleography, the inscription is dated not earlier than the first half of the 3d cent. and is а new important source of the problem of the presence of the Rome Army veterans among the civil population of the Chersonese. Certain features of the language of the epitaph and its design exhibit typical properties of the process of the Chersonese population Romanization in the first centuries А. D.